Insights into Cataract Surgery Outcomes in Age-Related Macular Degeneration: Perspectives across Severity Grades Under Clinical Routine Conditions - Hössl, Leopold; Vaghefi, Shirin Ashraf; Riemer, Tommes; Kabiri, Payam; Bonaventura, Theresa; Rübsam, Anne; Joussen, Antonia M; Zeitz, Oliver (Ophthalmology retina, 2025)
Cataract and age-related macular degeneration (AMD) share age as a main risk factor and thus have a high coincidence. Both conditions substantially reduce visual acuity. This study aimed to assess the impact of cataract surgery on visual acuity, retinal morphology, and VEGF inhibitor therapy in patients with AMD. This study was designed as a retrospective, monocentric, real-world study. Patients diagnosed with either dry AMD or neovascular AMD undergoing cataract surgery at Charité Campus Benjamin Franklin. Treatment data were extracted from the Berlin Macular Registry. Best-corrected visual acuity (BCVA) and macular OCT parameters, including central retinal thickness (CRT), macular volume (MV), presence of macular edema, intraretinal or subretinal fluid, and pigment epithelial detachment were assessed. The primary outcome measure was the postoperative BCVA. Secondary outcomes included postoperative CRT, MV, changes in qualitative OCT parameters, alterations in anti-VEGF-therapy interval, and postoperative complications. A total of 418 eyes of 418 patients were included in the analysis with a mean follow-up time of 18.8 (2-62) months. They were classified into a neovascular AMD (n = 85) and a dry AMD (n = 333) cohort. Mean BCVA improved significantly in the neovascular AMD cohort from 0.69 ± 0.45 logarithm of the minimum angle of resolution (logMAR) to 0.47 ± 0.42 (P < 0.001) and in the dry AMD cohort from 0.53 ± 0.47 logMAR to 0.27 ± 0.32 (P < 0.001) at the 2-month follow-up. Improvements in BCVA were sustained to the final visit (18.8 ± 19.5 months after surgery) with BCVA at 0.46 ± 0.38 logMAR (P < 0.001) and 0.26 ± 0.34 logMAR (P < 0.001), respectively. Temporary postoperative increases in CRT and MV were observed, reverting to preoperative levels by 6 months after surgery. The need for anti-VEGF therapy did not change postoperatively in patients with neovascular AMD. Within this retrospective analysis, on average, patients with coincident AMD of all severity grades meeting the inclusion criteria benefited from cataract surgery. Transient increases in retinal thickness and MV returned to baseline within 6 months after surgery. The need for intravitreal injections in neovascular AMD subjects was unchanged after surgery. Overall, the study suggests no adverse long-term macular changes attributable to cataract surgery. Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.